Predicting vegetative phase nutrient uptake in Cannabis sativa L. via transpiration-driven mass-balance - Powell, Kit; Bauerle, William L. (Frontiers in Plant Science, 2026)
The rapid expansion of Cannabis sativa L. cultivation necessitates fertilization strategies that optimize nutrient delivery and resource use. A transpiration-driven mass balance framework quantified nutrient removal from solution relative to whole-plant water use in two Cannabis sativa L. cultivars, CJ2 and First Light. Uptake measured via the pour-through method was compared against total and organ-specific tissue concentrations, verifying cultivar-specific mass balance nutrient uptake estimates. The objective was to formulate a nutrient replenishment strategy proportional to water uptake, enabling continuous, cultivar-specific fertilization optimization. Results revealed cultivar-specific uptake patterns: nitrogen ranged from 97–155 mg L-1 (First Light) and 78–145 mg L-1 (CJ2); phosphorus from 14–48 mg L-1 and 13–49 mg L-1; and potassium from 112–216 mg L-1 and 111–205 mg L-1, respectively. Water use efficiency (WUE) was similar across cultivars (CJ2: 4.71 g L-1 H2O; First Light: 4.59 g L-1 H2O). Temporal analysis normalized to transpired water showed peak nitrogen and potassium uptake during week 1, with significant declines by week 2 (p < 0.001), while calcium and magnesium uptake increased steadily (p < 0.0001). These findings support a scalable nutrient forecasting method based on nutrient uptake from solution that is proportional to whole-plant water use. Integrating transpiration data with tissue nutrient profiles enables cultivar-specific fertigation strategies that minimize waste and enhance sustainability in cannabis production.